Health consequences of combined oral contraceptives - Hannaford, P. (British medical bulletin, 2000)
During the past 40 years, combined oral contraceptives (COCs) have become a key component of modern fertility regulation programmes. Today, an estimated 100 million women throughout the world use this method of contraception. With such wide-spread usage, it is perhaps not surprising that COCs have been the subject of extensive medical research.